Bisphenols and Male Reproductive Health: From Toxicological Models to Therapeutic Hypotheses - De Toni, Luca; De Rocco Ponce, Maurizio; Petre, Gabriel Cosmin; Rtibi, Kais; Di Nisio, Andrea; Foresta, Carlo (Frontiers in Endocrinology, 2020)
Bisphenols, and in particular bisphenol A (BPA), have been widely used for the production of plastic manufacts in the last 50 years. Currently, BPA is present in a variety of daily use polycarbonate plastics and epoxy resins and dietary ingestion is considered the main route of human exposure. Accordingly, BPA is the chemical pollutant with the widest exposure in humans, involving nearly 90% of general population, according to recent studies. Concerns about BPA effects on human health date back to 1930’s, when severe impact on male sexual development was suggested. Now, the acknowledged biological effects of BPA are various. In regards to human fertility, BPA has been shown to disrupt hormone signaling even at low concentrations. Results from human epidemiological studies have reported BPA interference with follicle stimulating hormone, inhibin B, estradiol, testosterone levels and sexual function in male subjects. Moreover, recent studies have reported an association between BPA levels and reduced sperm concentration, motility, normal morphology, sperm DNA damage and altered epigenetic pattern, resulting in trans-generational legacy of BPA effects. In this review, the recognized effects of BPA on male reproductive health are described, from the most recent issues on experimental models to epidemiological data. In addition, the very recent interest about the use of nutraceutical remedies to counteract BPA effects are discussed.